Heterogeneity in Trajectories of Life Satisfaction After Reunification: The Role of Individual Resources and Life Stage in Former East Germany - Martin Wetzel; Jonathan Wörn; Bettina Hünteler; Karsten Hank (Social Indicators Research, 2021)
For people living in the former East Germany, reunification with the former West Germany fundamentally transformed the sociopolitical system and most domains of everyday life. Previous research has revealed temporal shifts in average life satisfaction after reunification in the former East German population as a whole, but so far little is known about heterogeneity in patterns of adjustment within the population. Building on evidence of considerable diversity in trajectories of adjustment to other critical life events, in the current study we use longitudinal data from the German Socio-Economic Panel Study and growth mixture models to identify typical yet distinct trajectories of life satisfaction among former East Germans, covering the period just before reunification and four years thereafter. We identified four trajectories: continuously satisfied (experienced by 17% of the sample), upward adjusters (24%), downward adjusters (34%), and continuously dissatisfied (25%). Results of logistic regression analyses indicate that the propensity to follow a particular trajectory was strongly predicted by an individual's baseline economic (employment, but not income), socio-relational (loneliness) and personal (education, satisfaction with health) resources. Whereas former East Germans with more resources just prior to reunification were more likely to maintain high or increase in life satisfaction, their peers with fewer resources were more apt to either maintain low or decrease in life satisfaction. People in their mid-twenties through mid-fifties (i.e., prime working age) at the time of reunification were also more likely to maintain low life satisfaction. Accordingly, reunification affected the unfolding of individual lives differently.
Keywords: 300; German reunification; Adjustment; Well-being; Critical life event; Life course; Growth mixture model